2000
DOI: 10.2337/diabetes.49.5.863
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine activates the plasminogen activator inhibitor 1 gene promoter through Sp1 DNA binding sites in glomerular mesangial cells.

Abstract: Increased flux through the hexosamine biosynthetic pathway is associated with altered gene expression. To investigate the underlying mechanisms, we treated glomerular mesangial cells with glucosamine and studied the regulation of the plasminogen activator inhibitor (PAI)-1 gene. Incubating mesangial cells with 2 mmol/l glucosamine for 4 days resulted in a 3.1 ± 0.4-fold increase in PAI-1 mRNA levels (P < 0.01) and a 33 ± 9-fold increase in the activity of a transiently transfected PAI-1 promoter-luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 69 publications
4
79
0
1
Order By: Relevance
“…The activation of AP-1 in the GT1 cells was specific, as we found no enhanced nuclear content or DNA-binding activity of other transcription factors that have been linked to high glucoseϪinduced promoter activation, such as Sp-1 (25,31) or cAMP-responsive element binding protein (CREB)/activating transcription factor (ATF) 1 (34). Determination of Sp-1 in the same nuclear extracts that were used for studies on AP-1 revealed changes in neither the amount of Sp-1 protein (Fig.…”
Section: Glut1 Overexpression Induces Ap-1 and Pkcmentioning
confidence: 80%
See 1 more Smart Citation
“…The activation of AP-1 in the GT1 cells was specific, as we found no enhanced nuclear content or DNA-binding activity of other transcription factors that have been linked to high glucoseϪinduced promoter activation, such as Sp-1 (25,31) or cAMP-responsive element binding protein (CREB)/activating transcription factor (ATF) 1 (34). Determination of Sp-1 in the same nuclear extracts that were used for studies on AP-1 revealed changes in neither the amount of Sp-1 protein (Fig.…”
Section: Glut1 Overexpression Induces Ap-1 and Pkcmentioning
confidence: 80%
“…The hyperglycemia-induced TGF-␤ stimulates the production of fibronectin and other matrix proteins in mesangial and other renal cells (8,9,22). Activation of protein kinase C (PKC) isoforms (7,10,23), the hexosamine biosynthetic pathway (24,25), and the extracellular signalrelated kinase (ERK) 1 and 2 (26,27) and p38 mitogenactivated protein kinase (MAPK) pathway (28,29) have been implicated in the enhanced expression of TGF-␤1 and matrix proteins. Of note, the hyperglycemia-enhanced generation of reactive oxygen species (ROS) has been linked to the activation of PKC (30) and the hexosamine pathway (31) and to enhanced TGF-␤1 synthesis (31,32).…”
mentioning
confidence: 99%
“…Although this pathway was reported to mediate many of the effects of high glucose level via the synthesis of fructose 6-phosphate (26,40,46), the importance of glutamine has been neglected until now. Indeed, to our knowledge, the involvement of the hexosamine pathway in the effect of glutamine has not been studied on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…phosphorylation and glycosylation (37,38). Concerning O-glycosylation, Sp1 was shown to be a target of the hexosamine pathway (26,34), but the increase in glycosylation could both stimulate or inhibit its transcriptional activity (39 -42) (for review, see also Refs. 43 and 44).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of O-GlcNAc has been shown to affect rates of proteasomal degradation and transcriptional activity of Sp1 (15,42). The effects of glucose on regulation of plasminogen activator inhibitor 1 and transforming growth factor-␤, proteins that are thought to play a role in the complications of diabetes, have also been shown to correlate with the degree of Sp1 glycosylation (43). Third, O-linked GlcNAc modification of endothelial nitrogen oxide synthase (eNOS) was recently demonstrated; these findings were used to explain the nonresponsiveness of eNOS to insulin stimulation in diabetes (16).…”
Section: Figmentioning
confidence: 99%